Communication among selected members improves cooperation in a social dilemma - Kitakaji, Yoko; Hizen, Yoichi; Ohnuma, Susumu (Frontiers in Behavioral Economics, 2025)
Communication is crucial to resolving conflicts such as social dilemmas. Previous literature concurs that communication among all group members increases cooperation. However, gathering all the members is often difficult. Hence, the effect of communication among some group members needs to be examined. The current study addressed this notion in a public goods experiment framework measuring the social value orientation of individuals. We conducted a six-person public goods game 20 times with members fixed. Between the 10th and 11th periods, we implemented different communication tactics: communication among all members, communication among three members selected randomly, or no communication (control). We observed that communication among some members increased the cooperation rate compared to no communication; however, the effect was weaker when compared with communication among all the members. Furthermore, partial communication increased the cooperation rate of prosocial individuals regardless of whether to join the communication process themselves. Proself individuals, on the contrary, cooperated as long as they communicated. Non-communicating members did not decrease their perception of goal-sharing and reciprocity compared to communicating members. These observations affirm that communication among some members is beneficial, even if assembling all the members is not always feasible.